INFLUENCE OF KILOHERTZ-FREQUENCY ALTERNATING CURRENTS (KFAC) AND PULSED CURRENTS (PC) ON THE RELATIVE RECRUITMENT OF MOTOR AND SENSORY AXONS (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2025)
CONTEXTUALIZAÇÃO: Neuromuscular electrical stimulation (NMES) is effective for reducing pain and improving strength in individuals with neuromuscular diseases, helping prevent muscle atrophy and weakness. The primary types of NMES are low-frequency pulsed current (PC) and kilohertz-frequency alternating current (KFAC), with KFAC generating more torque due to longer burst durations. Phase duration impacts neuromuscular activation and discomfort more than frequency. The Hoffmann reflex (H reflex) aids in assessing motor recruitment, but optimal parameters for effectiveness remain unclear.  OBJETIVOS: To compare different parameters of low and medium frequency currents in motor and peripheral recruitment and jointly evaluate sensory discomfort. MÉTODOS: This randomized, double-blind trial, approved by the Research Ethics Committee of the University of Brasília (CAAE: 72475623.9.0000.809), investigated the effects of various NMES protocols on motor recruitment and sensory discomfort. Two meetings were held, with a 7-day interval, to apply NMES to the tibial nerve in the popliteal fossa region. The study involved young, healthy adults (18-45 years) who were physically active, with exclusions for musculoskeletal conditions or other factors that could interfere with the study. The independent variables included four KFAC currents with varying frequencies and pulse durations, and a single-phase current. The dependent variables assessed were maximum voluntary joint torque, M-wave, H-reflex, sensory discomfort (VAS), and recruitment curves. In the first meeting, participants were familiarized with the procedure and randomized to receive different NMES protocols. In the second meeting, warm-up, M-wave and H-reflex measurements, and sensory discomfort were recorded. Materials used in the study included a high-voltage stimulator (DIGITIMER, DS8R), portable electromyography system (MP160, Biopac), and isokinetic dynamometer (BIODEX 4 system). Statistical analysis was performed using Generalized Estimating Equations (GEE), with a sample size of 30 participants, determined via G Power. The study aimed to understand the impact of NMES on muscle activation and discomfort in rehabilitation settings. RESULTADOS: This study shows that, despite differences in pulse duration and frequency, low-frequency pulsed currents (PC) and kilohertz-frequency alternating currents (KFAC) lead to similar neuromuscular activation regarding motor unit recruitment and H-reflex modulation. The findings suggest that pulse width has a stronger effect than frequency on neuromuscular responses, especially in determining the intensity needed for maximal motor responses. Moreover, no significant differences in sensory discomfort were found between PC and KFAC, challenging the belief that kilohertz-frequency currents are more comfortable. CONCLUSÕES: The findings of this study highlight that, despite differences in pulse duration and frequency between low-frequency pulsed currents (PC) and kilohertz-frequency alternating currents (KFAC), both stimulation types similarly affect motor unit recruitment and central nervous system activation. IMPLICAÇÕES: These findings suggest that, in clinical practice, optimizing NMES parameters should prioritize pulse width over frequency to enhance motor recruitment while minimizing discomfort. Future studies should explore these effects in clinical populations to determine their relevance for rehabilitation strategies.